Deep Learning Approach for Pole like Road object Detection Using LiDAR–Orthophoto Fusion - Payal, Payal; Kaur, Rasneet (International Journal of Computer Sciences and Engineering, 2020)
With the growth of computer vision, digital image processing is necessary to provide a clear image to the user. In existing research detection of pole side objects with the help of an LiDar which only detect the object but not with clear transparency in proposed research we are try to give the clear vision of the pole side object with the help of fusion of LiDar and orthophoto and also improve the accuracy of an image.